Aktivitas Public Relations Dinas Sosial Kota Tangerang Selatan pada Hari Disabilitas Internasional Bersama Rumah I’m Star - Susan Ary Ayu Anjani; Istisari Bulan Lageni; Nani Nurani Muksin (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
People with disabilities continue to experience barriers in accessing education, employment, and social participation, requiring active government involvement through inclusive programs. One such initiative is the International Disability Day event organized by the South Tangerang City Social Service in collaboration with Rumah I’m Star. This study aims to analyze the public relations activities of the South Tangerang City Social Service by examining problem identification, planning, implementation, and interpretation in organizing the event. The research is based on the public relations model of Cutlip, Center, and Broom, which includes four stages: defining the problem, planning and programming, taking action and communicating, and evaluating the program. A qualitative approach with a descriptive method was employed. Data were collected through interviews, observations, and documentation, involving purposively selected informants from the Public Relations Division of the Social Service, the founder of Rumah I’m Star, beneficiaries, and public relations experts. The findings show that the Social Service identified low public awareness of disability issues as the main problem and responded by developing a collaborative communication strategy with Rumah I’m Star. The activities implemented included art performances, talk shows, and a bazaar showcasing the works of persons with disabilities, which were disseminated digitally. Program evaluation was conducted internally without standardized measurement instruments, limiting interpretation to event outcomes and participant involvement. Overall, the study concludes that these public relations efforts enhanced government communication and promoted inclusion awareness, although broader public engagement is needed for sustainable impact.